Inclusion of steps to enhance mucus clearance may provide benefit for symptomatic COVID patients by reducing total viral load, time to recovery, risk of complications and transmission risk - John Given; Charles Steele (Open Journal of Asthma - Peertechz Publications, 2021)
The COVID pandemic brought healthcare systems close to the breaking point and stimulated research which has led to an effective vaccine, but no reliably effective antiviral medication to treat active infection. A prioritization of transmission risk reduction has emphasized patient isolation and PPE for healthcare workers and others. Clinical management improved somewhat with inclusion of corticosteroid but remained primarily supportive in nature. Mucus mobilization has not been perceived as a priority for preventing or treating disease. Furthermore, proning ventilated patients is practiced intermittently and is not prioritized in managing ventilated patients, as it is rarely recommended. Mucociliary clearance (MCC) forms the backdrop for a mucocentric perspective on COVID and other respiratory conditions. Objective measures of MCC and mucus burden are lacking, but it is likely these factors that play a significant role in infection risk and variability of clinical course. The identified high-risk groups share a feature of impaired awareness and response to the presence of excess mucus. While further research is needed, safe and cost-effective steps based on improving MCC are available for immediate implementation: these include strategic body positioning, upper respiratory care, refinement of cough technique and airway hydration.